Thyroid surgery before the technologic revolution: from Samuel Gross’ “torrents of blood” to Paolo Miccoli’s video-assisted thyroidectomy: A history of Thyroid surgery before the 2.0-Era - Minuto, Michele N; Bertoglio, Sergio; Varaldo, Emanuela (Medicina Historica, 2019)
“Can the thyroid gland…be removed with a reasonable hope of saving the patient?…If a surgeon should be so foolhardy as to undertake it…every step he takes will be followed by a torrent of blood, and lucky will it be for him if his victim live long enough to enable him to finish his horrid butchery…no honest and sensible surgeon would ever engage in it”. With this renowned posthumous declaration, in 1886, Samuel D. Gross proposed that thyroid surgery should have been abandoned by surgeons. Despite this, subsequent improvements in anesthesiology, antisepsis strategies and better surgical instruments allowed to significantly decrease the mortality rates of this surgery to nearly zero percent, as is the case now. This paper aims at highlighting the most important steps and Mentors that led thyroid surgery to become one of the safest and most widespread surgical procedures.